2019
DOI: 10.1111/resp.13513
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physical activity during hospital admission for chronic respiratory disease

Abstract: Background and objective: Establishing the amount of inpatient physical activity (PA) undertaken by individuals hospitalized for chronic respiratory disease is needed to inform interventions. This observational study investigated whether PA changes when a person is an inpatient, how long is required to obtain representative PA measures and whether PA varies within a day and between patients of differing lengths of stay. Methods: A total of 389 participants were recruited as early as possible into their hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…There is no published consensus on how many days and hours of data are required to capture representative data in an HD population, but our findings align with work in other populations living with long-term conditions. A single day of at least 11 h data was representative of PA in a cohort of inpatients living with Chronic Obstructive Pulmonary Disease, as activity restriction enforced by hospitalisation (comparable to an HD day) reduced variability in step count [38]. In the same population, in free-living conditions (akin to non-HD days in the current study), 4 days of at least 8 h of wear time have been recommended [22].…”
Section: Discussionmentioning
confidence: 99%
“…There is no published consensus on how many days and hours of data are required to capture representative data in an HD population, but our findings align with work in other populations living with long-term conditions. A single day of at least 11 h data was representative of PA in a cohort of inpatients living with Chronic Obstructive Pulmonary Disease, as activity restriction enforced by hospitalisation (comparable to an HD day) reduced variability in step count [38]. In the same population, in free-living conditions (akin to non-HD days in the current study), 4 days of at least 8 h of wear time have been recommended [22].…”
Section: Discussionmentioning
confidence: 99%
“…Orme et al . showed that patients, who were hospitalized for an acute COPD exacerbation, walked, on average, only ~600 steps/day, which did not improve over the course of their hospitalization despite improvements in their clinical condition. Together, these data highlight the pressing need to develop and implement interventions to encourage mobility and enhance physical activity of COPD patients especially during exacerbations.…”
Section: Reduced Mobility: a Major Concern During And Following Exacementioning
confidence: 99%
“…Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) are clinically impactful events characterised in their pulmonary component by heightened respiratory symptoms (dyspnoea, cough and sputum production) 1 and in their extrapulmonary components by musculoskeletal dysfunction, 2 muscle weakness 3 and decreased physical activity levels. [4][5][6] Pulmonary rehabilitation (PR) comprising multidisciplinary evaluation, physical exercise training and education/psychological support 7 is one of the most effective therapies to improve important health outcomes in this patient group when applied during the period of disease stability 8 and shortly following AECOPD. 9 International guidelines recommend PR to commence within 2-4 weeks of discharge, [10][11][12] however rates of referral, uptake and completion of PR following AECOPD are suboptimal.…”
Section: Introductionmentioning
confidence: 99%